Experiences of parents whose sons or daughters have (had) attempted suicide. (11th September 2013) - Buus, Niels; Caspersen, Jimmy; Hansen, Rasmus; Stenager, Elsebeth; Fleischer, Elene
Abstract Aim The aim of this exploratory study was to gain further insights into the experiences of parents of sons or daughters who have attempted suicide and how these parents respond to the increased psychosocial burden following the suicide attempt(s). Background Suicide is a major public health problem and relatives are understood as playing an important role in suicide prevention; however, suicide and suicidal behaviour affect the relatives' lives profoundly, both emotionally and socially, and the psychosocial impact on families is underresearched. Design Focus groups with parents of sons or daughters who have attempted suicide. Methods In January and February 2012, we interviewed two groups of parents recruited at a counselling programme for relatives of persons who have attempted suicide. The analysis combined a thematic analysis with a subsequent analysis of how the themes were negotiated in the conversational interactions. The findings were interpreted and discussed within an interactionist framework. Findings The participants in the study described their experiences as a double trauma, which included the trauma of the suicide attempt(s) and the subsequent psychosocial impact on the family's well‐being. The pressure on the parents was intense and the fundamentally unpredictable character of suicide attempts was frequently emphasized. Conclusion Being the parent of a child who attempts suicide meant managing a life‐threatening situation and the additional moral stigma. In part, the participants did this in the group by negotiating the character of the suicide attempt(s) and who was responsible.